English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

((2x+5)/3) - (1/6) = (x/9) solve for x.

2007-06-10 12:48:13 · 9 answers · asked by poker22only 2 in Science & Mathematics Mathematics

9 answers

(2x+5)/3 - 1/6=x/9 making the denominator of 18
6(2x+5)/18-3/18=2x/18
(12x+30-3)/18=2x/18 multiplying by 18
12x+27=2x
10x=-27
x=-2.7
Checking the math
(2(-2.7) +5))/3-1/6=-2.7/9
(-5.4+5)/3 -1/6=2.7/9 again making the denominator 18
6(-.4)/18-3/18=2(2.7)/18 multiply by 18
-2.4-3=-5.4
checks out

2007-06-10 12:57:03 · answer #1 · answered by gordonmorrison 6 · 0 0

6.(2x + 5) - 3 = 2x
12x + 30 - 3 = 2x
10x = - 27
x = - 27 / 10

2007-06-11 05:13:34 · answer #2 · answered by Como 7 · 0 0

((2x+5)/3) - (1/6) = (x/9)

Multiply thru by 18

12x + 30 - 3 = 2x

10x = -27

x = -27/10 = -2.7
.

2007-06-10 12:55:40 · answer #3 · answered by Robert L 7 · 0 0

we are given that ((2x+5))/3 - 1/6 = x/9
Combine the variable one side.
that is,
((2x+5))/3 - x/9 = 1/6, since add both sides by 1/6.
Take the LCM on left side.
(3(2x+5) - x)/9 = 1/6
6x +15 -x = 9/6
5x + 15 = 3/2
5x = 3/2 -15
5x = (3-30)/2
5x = -27/2
x = -27/10 = -2.7
_____________________________________________
For more assistance please visit www.classof1.com
Classof1 - leading web tutoring and homework help.
Toll free - 1877-252-7763

2007-06-10 13:07:59 · answer #4 · answered by Anonymous · 0 0

I'd start by multiplying everything by 9

3(2x+5)-3/2=x
6x+15-x=3/2
5x=3/2-15
x=3/10-3
x= -2.7

2007-06-10 12:53:18 · answer #5 · answered by sdenison1983 3 · 0 0

((2x+5)/3) - (1/6) = (x/9)
(2(2x+5)/6) - (1/6) = (x/9)
(4x+10-1)/6 = (x/9)
(4x+9)/6 = (x/9)
9(4x+9) = 6x
36x+81 = 6x
36x-6x = 81
30x = 81
x = 81/30
x = 2.7

2007-06-10 13:49:13 · answer #6 · answered by Kemmy 6 · 0 1

((2x+5)/3)-(1/6)=(x/9)
(4x+10)/6-1/6=x/9
(4x+10-1)/6=x/9
(4x+9)/6=x/9
(4x+9)x9=x x 6
36x+81=6x
36x-6x=-81
30x=-81
x=-81/30
x=-27/10

2007-06-10 15:48:47 · answer #7 · answered by sam 3 · 0 0

i Had a problem like this in number sense. count how many of the numbers there are, then multiply the number by the number in the exact middle fo the string

2016-05-17 04:39:47 · answer #8 · answered by ? 3 · 0 0

I AGREE ON THE PERSON WHO ANSWERS YOUR QUESTION FIRST, X= - 2.7

2007-06-10 12:57:38 · answer #9 · answered by Den 2 · 0 0

fedest.com, questions and answers